Dopamine D2 receptor gene polymorphisms and externalizing behaviors in children and adolescents - Osmar Henrique Della Torre; Lúcia Arisaka Paes; Taciane Barbosa Henriques; Maricilda Palandi de Mello; Eloisa Helena Rubello Valler Celeri; Paulo Dalgalarrondo; Gil Guerra-Júnior; Amilton dos Santos-Júnior (BMC, 2018)
Abstract Background Dopamine is involved in several cerebral physiological processes, and single nucleotide polymorphisms (SNP) in the dopamine D2 receptor gene (DRD2) have been associated with numerous neurological and mental disorders, including those involving alterations in cognitive and emotional processes. Methods The aim of this study was to evaluate the association between the SNPs c.957C > T (rs6277) and c.-585A > G (rs1799978) in the DRD2 gene and behavioral characteristics of children and adolescents based on an inventory of the Child Behavior Checklist (CBCL). Children and adolescents between 8 and 20 years old who were clinically followed-up were genotyped for the SNPs c.957C > T and c.-585A > G, and related to data of the CBCL/6-18 scale assessment performed with the help of caregivers. The chi-squared test was used to assess the differences in the frequencies of the C and T alleles in the polymorphism c.957C > T and of the A and G alleles in the polymorphism c.-585A > G with respect to the grouped CBCL scores at a significance level of 5%. Multiple logistic regression models were performed, to control whether sex and/or ethnicity could influence the results. Results Eighty-five patients were assessed overall, and the presence of the T allele (C/T and T/T) of DRD2 c.957C > T polymorphism was found to be significantly associated with the occurrence of defiant and oppositional problems and with attention and hyperactivity problems. There were no associations detected with polymorphism DRD2 c.-585A > G polymorphism. Both SNPs were in Hardy-Weinberg-equilibrium. Conclusions Although the findings of this study are preliminary, due to its small number of participants, the presence of T allele (C/T, T/T) in c.957C > T SNP was associated with difficulty in impulse control, self-control of emotions, and conduct adjustment, which can contribute to improving the identification of mental and behavioral phenotypes associated with gene expression.